Single incision laparoscopic surgery in gynecology: Evolution, current trends, and future perspectives - Bernard Su Min Chern; Smita Lakhotia; Chong Kiat Khoo; Anthony Yew Ming Siow (Wolters Kluwer Medknow Publications, 2012)
Minimally invasive surgery has become the standard of care for different procedures in various subspecialties. Single-incision laparoscopic surgery (SILS) is a rapidly developing field that may mark the new frontier in laparoscopy. The ongoing and continuous efforts to decrease morbidity and improve cosmesis from laparoscopic surgery has led to minimization in number and size of ports required for these procedures. SILS is laparoscopic surgery performed through a single, small skin incision 15-20 mm in size, usually hidden in the umbilicus. SILS is not a new endeavor, but recent advances in conventional laparoscopic techniques and instrumentation has made SILS more feasible and safer for patients. Within a short span of time there has been an increase in the number of studies and clinical reports depicting the use of SILS in gynecology. As this novel field moves forward, a review of its evolution and current status is requisite. The objective of this article is to review the contemporary literature on SILS in gynecology and the recent advances in techniques and instrumentation used in SILS. The ongoing refinement of surgical techniques and instrumentation has resulted in increasing use of SILS across many subspecialties. Recently published studies have proven the feasibility, safety, and reproducibility of SILS in various gynecologic procedures.